Euro Currency Risk and the Geography of Debt Flows to Peripheral European Monetary Union Members - Ersal-Kiziler, Eylem; Nguyen, Ha (World Bank, Washington, DC, 2016)
The pattern of debt flows to peripheral European Monetary Union members seems puzzling: they are mostly indirect and channeled through the large countries of the European Monetary Union. This paper examines to what extent the introduction of the euro and the elimination of the intra-area currency risk can explain this puzzle. A three-country dynamic stochastic general equilibrium framework with endogenous portfolio choice and two currencies is developed. In the equilibrium, the core members of the European Monetary Union emerge as the main group of lenders to the peripheral European Monetary Union members. Outside lenders are pushed from the periphery debt markets because of currency risk. The model generates a pattern of debt flows consistent with the data despite the absence of any exogenous frictions or market segmentations.